Degradation of metaldehyde in water by nanoparticle catalysts and powdered activated carbon - Li, Zhuojun; Kim, Jong Kyu; Chaudhari, Vrushali; Mayadevi, Suseeladevi; Campos, Luiza C. (Environmental Science and Pollution Research, 2017)
Metaldehyde, an organic pesticide widely used in the UK, has been detected in drinking water in the UK with a low concentration (< 1 mu g L-1) which is still above the European and UK standard requirements. This paper investigates the efficiency of four materials: powdered activated carbon (PAC) and carbon-doped titanium dioxide nanocatalyst with different concentrations of carbon (C-1.5, C-40, and C-80) for metaldehyde removal from aqueous solutions by adsorption and oxidation via photocatalysis. PAC was found to be the most effective material which showed almost over 90% removal. Adsorption data were well fitted to the Langmuir isotherm model, giving a q (m) (maximum/saturation adsorption capacity) value of 32.258 mg g(-1) and a K-L (Langmuir constant) value of 2.013 L mg(-1). In terms of kinetic study, adsorption of metaldehyde by PAC fitted well with a pseudo-second-order equation, giving the adsorption rate constant k(2) value of 0.023 g mg(-1) min(-1), implying rapid adsorption. The nanocatalysts were much less effective in oxidising metaldehyde than PAC with the same metaldehyde concentration and 0.2 g L-1 loading concentration of materials under UV light; the maximum removal achieved by carbon-doped titanium dioxide (C-1.5) nanocatalyst was around 15% for a 7.5 ppm metaldehyde solution.